Archaeological Research at the Lvov University: Interwar Period - Bilas, Natalia (Archaeopress Archaeology, 2018)
Fundamentals of archaeological education were laid out at Lvov University in the second half of the 19th century. Along with the Stavropegial Institute and Shevchenko Scientific Society the University became one of the largest centers of archaeological research in Eastern Galicia.1 The interwar period – when whole former Galicia was part of the Second Republic of Poland – contributed to the history of development of archaeological education in the result of the efforts of two distinguished scholars – Edmund Bulanda and Leon Kozłowski. The article focuses on the establishment and activities of the Department of Archaeology and History of Material Culture and the Prehistory Department with a special review of Polish lands prehistory of Jan Kazimierz University of Lvov. This paper discusses the reform of archaeological education at the University and organization of the academic procedures in the field of classical archaeology and prehistoric archaeology at the Philosophy/ Humanities Department
29 cm